Cross-cultural adaptation and psychometric evaluation of the Chinese version of Hospital Culture of Nursing Research Scale (CHCNRS): a translation and validation study - Chuang Li; You Bei Lin; Ran Qi; Ejercito Mangawa Balay-Odao; Lan Zhang (BMC Nursing)
Abstract Background The culture of nursing research forms a critical foundation for advancing the nursing discipline and enhancing the quality of nursing care. In the context of China’s unique healthcare environment and nursing practices, introducing localized tools that reflect cultural nuances is essential. Strengthening research capabilities, optimizing management systems, and promoting innovation and academic integrity tailored to Chinese hospitals are crucial for delivering improved patient care. Objective The Hospital Culture of Nursing Research Scale (HCNRS) assesses nurses’ perceptions of the nursing research culture within hospital settings. This study aimed to translate the HCNRS into Chinese and to evaluate the psychometric properties of this culturally adapted version to ensure its relevance and reliability in Chinese healthcare institutions. Methods A total of 766 clinical nurses were recruited for this study through convenience sampling, in accordance with Kendall’s sample size estimation method. The original scale was translated following Brislin’ s guidelines. The validity of the instrument was assessed through item analysis, structural validity, and reliability testing. Data analysis was conducted using SPSS and AMOS software. Results The Chinese version of the 32-item scale demonstrated good psychometric properties. Exploratory factor analysis identified five factors, accounting for 56.112% of the total variance. Confirmatory factor analysis showed excellent fit indices: CMIN/DF = 1.067, RMSEA = 0.012, GFI = 0.941, NFI = 0.919, IFI = 0.911, TLI = 0.994, and CFI = 0.994. Reliability measures were also robust, with a total Cronbach’s α coefficient of 0.906, and Retest reliability was 0.864. Conclusion The CHCNRS demonstrates strong psychometric properties and is well-suited for assessing Chinese nurses’ perceptions of the culture of nursing research in hospitals. Its application can inform hospital management strategies, support evidence-based policy-making, and promote a research-supportive environment in clinical settings. Clinical trial number Not applicable.